Hyperpolarisation-activated cyclic nucleotide-gated channels regulate the spontaneous firing rate of olfactory receptor neurons and affect glomerular formation in mice - Nakashima, Noriyuki (Blackwell Science Inc, 2013)
Olfactory receptor neurons (ORNs), which undergo lifelong neurogenesis, have been studied extensively to understand how neurons form precise topographical networks. Neural projections from ORNs are principally guided by the genetic code, which directs projections from ORNs that express a specific odorant receptor to the corresponding glomerulus in the olfactory bulb. In addition, ORNs utilise spontaneous firing activity to establish and maintain the neural map. However, neither the process of generating this spontaneous activity nor its role as a guidance cue in the olfactory bulb is clearly understood. Utilising extracellular unit-recordings in mouse olfactory epithelium slices, we demonstrated that the hyperpolarisation-activated cyclic nucleotide-gated (HCN) channels in the somas of ORNs depolarise their membranes and boost their spontaneous firing rates by sensing basal cAMP levels; the odorant-sensitive cyclic nucleotide-gated (CNG) channels in cilia do not. The basal cAMP levels were maintained via the standing activation of β-adrenergic receptors. Using a Tet-off system to over-express HCN4 channels resulted in the enhancement of spontaneous ORN activity and dramatically reduced both the size and number of glomeruli in the olfactory bulb. This phenotype was rescued by the administration of doxycycline. These findings suggest that cAMP plays different roles in cilia and soma and that basal cAMP levels in the soma are directly converted via HCN channels into a spontaneous firing frequency that acts as an intrinsic guidance cue for the formation of olfactory networks.